Gratitude as Predictor of Turnover Intention: In the Context of Javanese: Gratitude Sebagai Prediktor Intensi Turnover : Dalam Konteks Suku Jawa - Hidayah, Fathul (Psikologia : Jurnal Psikologi, 2019)
The purpose of this study is to see gratitude influence to turnover intention in Javanese. There are 51 people research subjects who are already working with an age range of 23-53 years in both public and privat organizations (BUMN, PNS, School, Entrepreneur). Research instruments use likert scale, it is gratitude and scale of turnover intention. After testing, it can be seen the results of this study show that there is significant value (sig = 0.012<0.05), that is mean gratitude has an influence on turnover intention in Javanese. In addition, the percentage of the role of gratitude in influencing the turnover intention of 12,1% whereas 87,9% influenced by other factors.